First Measurement of the |t| Dependence of Incoherent J/ψ Photonuclear Production - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2024)
The first measurement of the cross section for incoherent photonuclear production of J=ψ vector mesons as a function of the Mandelstam |t| variable is presented. The measurement was carried out with the ALICE detector at midrapidity, |y| < 0.8, using ultraperipheral collisions of Pb nuclei at a center-of-mass energy per nucleon pair of √ˢɴɴ = 5.02 TeV. This rapidity interval corresponds to a Bjorken-x rango (0.3–1.4) × 10¯³. Cross sections are given in five |t| intervals in the range 0.04 < |t| < 1 GeV² and compared to the predictions by different models. Models that ignore quantum fluctuations of the gluon density in the colliding hadron predict a |t| dependence of the cross section much steeper than in data. The inclusion of such fluctuations in the same models provides a better description of the data.
Keywords: Physics; Hadron; Rapidity; Range (aeronautics); Cross section (physics); Particle physics; Gluon; Meson; Nuclear physics; Quantum chromodynamics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03